TOO BUSY TO CARE?. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Jones, Debbie; McConaghy, Margaret; Haywood, Chris; Coackley, Alison
Abstract : Background: An increase in the complexity of patient's admitted to the Hospice and a greater use of acute interventions had resulted in staff feeling "too busy to care" with less time to provide high quality care . We recognised the need to change working practices to improve patient experience and staff satisfaction. After reviewing possible models and undertaking a scoping exercise, we agreed to implement the NHS Releasing Time to Care : The Productive Ward as a recognised quality initiative. This was previously restricted to hospital and community use, designed to help teams review working practices and minimise inefficient systems. This was supported at Network level in collaboration with 5 other Hospices. Aims: Increase Time for Caring therefore improving patient experience Improve departmental/inter-departmental communication Improve patient /staff environment Improve staff satisfaction Approach used: Network support Enhanced team working Staff and senior management commitment Collaborative module implementation training Phased roll out Evaluation at steering group level Outcomes: Confirmed network funding in conjunction with other hospices Network training and support to empower staff Focus on collaborative approach, shared learning experience, making a wider impact than working in isolation Transparent care provision using quality measures Efficient staff working practices Cost effectiveness, efficient use of limited resources Improvement in communication across all services and local hospices Awareness of the importance of environment; little wins to improve patient care have a positive effect on staff morale Improved patient safety and standard of care evidenced by quality measures Benefit at local, organisational and network level Application to Hospice Practice: Improved collaboration and networking Useful toolkit that has impacted on time for caring making a difference to patient experience and staff satisfaction Transferability Supports integrated working